LTE handover design for cellular-connected aircraft - Towhidlou, Vahid; Al-Rubaye, Saba; Tsourdos, Antonios (IEEE, 2022)
Ubiquitous accessibility worldwide and superior performance of cellular networks of communication like 4G and 5G make them a perfect candidate for air to ground (A2G) communications for low to medium altitude aircraft systems such as unmanned aerial vehicles (UAVs) and urban air mobility (UAM). However, cellular networks are designed and optimized for terrestrial users, and employing them communication of cellular connected aerial vehicles such as electric vertical take-off and landing (eVTOL) aircraft flying at higher altitudes and faster speeds is accompanied with some issues which should be resolved prior to application. Too many handovers and following consequences such as radio link failures, longer delays, and degraded throughput are major issues in wider employment of cellular networks for A2G communications. In this paper we have considered two main issues of handover in LTE networks when used for A2G communications of cellular-connected aircraft and have proposed novel handover algorithms addressing these issues which will decrease the number of unnecessary and ping pong handovers, as well as radio link failure rate for cellular connected aircraft. The improved performance of the proposed algorithms has been verified by extensive simulations in a bespoke designed simulation model for cellular connected aircraft served by LTE networks.
Keywords: UAV; UAM; eVTOL; Cellular Networks; 4G; LTE; Handover; Air to Ground Communications